2008
DOI: 10.1038/ni.1657
|View full text |Cite
|
Sign up to set email alerts
|

Triggering the succinate receptor GPR91 on dendritic cells enhances immunity

Abstract: Succinate acts as an extracellular mediator signaling through the G protein-coupled receptor GPR91. Here we show that dendritic cells had high expression of GPR91. In these cells, succinate triggered intracellular calcium mobilization, induced migratory responses and acted in synergy with Toll-like receptor ligands for the production of proinflammatory cytokines. Succinate also enhanced antigen-specific activation of human and mouse helper T cells. GPR91-deficient mice had less migration of Langerhans cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
422
1
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 415 publications
(465 citation statements)
references
References 28 publications
13
422
1
11
Order By: Relevance
“…A recent study showed that succinate acts as a chemokine, inducing MoDC migration in vitro [8]. DCs treated in the presence of succinate displayed enhanced migration to draining lymph nodes, demonstrating its chemotactic function.…”
Section: Succinate and Hif-1a In Inflammationmentioning
confidence: 98%
See 4 more Smart Citations
“…A recent study showed that succinate acts as a chemokine, inducing MoDC migration in vitro [8]. DCs treated in the presence of succinate displayed enhanced migration to draining lymph nodes, demonstrating its chemotactic function.…”
Section: Succinate and Hif-1a In Inflammationmentioning
confidence: 98%
“…For example, HIF-1a activation favors differentiation of T lymphocytes into proinflammatory Th17 cells and attenuates regulatory T cell development [7]. Importantly, as well as global changes in metabolism that occur in activated immune cells, individual metabolites, including succinate, citrate, and NAD + , have been demonstrated to possess signaling capacity and to influence immunity [4,8,9]. These somewhat surprising findings allow for metabolic changes occurring in inflammatory cells to serve as signals to which cells respond and can contribute to the inflammatory process ( Figure 2).…”
Section: Metabolic Alterations Influence the Immune Responsementioning
confidence: 99%
See 3 more Smart Citations